Enhancing language performance with non-invasive brain stimulation—A transcranial direct current stimulation study in healthy humans - Sparing, Roland; Dafotakis, Manuel; Meister, Ingo G.; Thirugnanasambandam, Nivethida; Fink, Gereon R. (Neuropsychologia, 2008)
In humans, transcranial direct current stimulation (tDCS) can be used to induce, depending on polarity, increases or decreases of cortical excitability by polarization of the underlying brain tissue. Cognitive enhancement as a result of tDCS has been reported. The purpose of this study was to test whether weak tDCS (current density, 57 μA/cm 2) can be used to modify language processing. Fifteen healthy subjects performed a visual picture naming task before, during and after tDCS applied over the posterior perisylvian region (PPR), i.e. an area which includes Wernicke's area [BA 22]. Four different sessions were carried out: (1) anodal and (2) cathodal stimulation of left PPR and, for control, (3) anodal stimulation of the homologous region of the right hemisphere and (4) sham stimulation. We found that subjects responded significantly faster following anodal tDCS to the left PPR ( p < 0.01). No decreases in performance were detected. Our finding of a transient improvement in a language task following the application of tDCS together with previous studies which investigated the modulation of picture naming latency by transcranial magnetic stimulation (TMS) and repetitive TMS (rTMS) suggest that tDCS applied to the left PPR (including Wernicke's area [BA 22]) can be used to enhance language processing in healthy subjects. Whether this safe, low cost, and easy to use brain stimulation technique can be used to ameliorate deficits of picture naming in aphasic patients needs further investigations.